PENGARUH PENGETAHUAN INVESTASI, MODAL MINIMAL INVESTASI DAN MOTIVASI INVESTASI TERHADAP MINAT MAHASISWA BERINVESTASI DI PASAR MODAL (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - M. Yusuf Alfandi Hasan; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2022)
This research is to determine the effect of investment knowledge, minimum investment capital, and investment motivation on student interest in investing in the capital market (a case study of students from the Faculty of Economics and Business at the University of Islam Malang). The independent variables in this study are investment knowledge, minimum investment capital, and investment motivation, while the dependent variable is student interest in investing in the capital market. This type of research is correlational research. The source of data is primary data with the data collection method in the form of a questionnaire. Based on this method, the number of students used there is 106 respondents. The hypotheses were tested using multiple linear regression analysis with SPSS Version 22. The results showed that the investment knowledge variable had a positive and significant effect on investment interest (0.000 < 0.05), and the minimal capital variable had a positive and significant effect on investment interest (0.00 < 0.05). In contrast, the investment motivation variable had no effect on investment interest (0.496 > 0.05).Keywords: Investment Knowledge, Minimum Investment Capital, Investment Motivation, Student Investment Interest